VEGFR-Mediated Cytotoxic Activity of Pulicaria undulata Isolated Metabolites: A Biological Evaluation and In Silico Study - Sameh S. Elhady (Life, 2021)
Natural products play a remarkable role not only in the synthesis, design, and discovery of new drugs but also as the most prominent source of drugs and bioactive substances. Adding to the search for new sources of safe innovative antitumor drugs, here we reported a phytochemical study on Pulicaria undulata which revealed promising antiangiogenic agents. Six compounds were isolated and identified as xanthoxyline (1), stigmasterol (2), oleanolic acid (3), salvigenin (4), rhamnetin (5) and dihydroquercetin-4′-methyl ether (6) using nuclear magnetic resonance (NMR) spectroscopic techniques. Compound 3 and 4 are first reported in Pulicaria genus. Both the extract and isolated compounds were evaluated for in vitro antiproliferative activity against breast cancer cell line (MCF-7). In vivo antiproliferative activity against Ehrlich’s ascites carcinoma (EAC) were also assessed. The P. undulata extract and isolates showed significant reduction in tumor weight, decreased both serum vascular endothelial growth factor B (VEGF-B) levels and vascular endothelial growth factor receptor 2 (VEGFR-2) expression significantly compared to the control EAC group, suggesting an antiangiogenic activity through the inhibition of VEGF signaling. Besides, they displayed reduction in CD34 expression, confirming their antiangiogenic effect. Moreover, the potential affinity of isolated compounds to human estrogen nuclear receptor-alpha (hER-α), the most recognized modulator of VEGFR-2 expression, was virtually estimated through molecular modeling studies. The most promising activity profiles were assigned to the investigated flavonoids, compounds 4–6, as well as the alkyl-phenylketone, compound 1. Additionally, these four top active compounds showed respective high to intermediate docking scores while possessing preferential binding with hER-α critical pocket residues. Based on the provided data, these isolated compounds illustrated promising inhibitors of VEGF-stimulated angiogenesis, which could be a possible mechanism for their anticancer activity.